Dynamic gadoxetate‐enhanced MRI for the assessment of total and segmental liver function and volume in primary sclerosing cholangitis. Issue 4 (10th October 2013) - Nilsson, Henrik; Blomqvist, Lennart; Douglas, Lena; Nordell, Anders; Jacobsson, Hans; Hagen, Karin; Bergquist, Annika; Jonas, Eduard
<x xml:space="preserve">Abstract</x> Purpose To evaluate dynamic hepatocyte‐specific contrast‐enhanced MRI (DHCE‐MRI) for the assessment of global and segmental liver volume and function in patients with primary sclerosing cholangitis (PSC), and to explore the heterogeneous distribution of liver function in this patient group. Materials and Methods Twelve patients with primary sclerosing cholangitis (PSC) and 20 healthy volunteers were examined using DHCE‐MRI with Gd‐EOB‐DTPA. Segmental and total liver volume were calculated, and functional parameters (hepatic extraction fraction [HEF], input relative blood‐flow [irBF], and mean transit time [MTT]) were calculated in each liver voxel using deconvolutional analysis. In each study subject, and incongruence score (IS) was constructed to describe the mismatch between segmental function and volume. Among patients, the liver function parameters were correlated to bile duct obstruction and to established scoring models for liver disease. Results Liver function was significantly more heterogeneously distributed in the patient group (IS 1.0 versus 0.4). There were significant correlations between biliary obstruction and segmental functional parameters (HEF rho −0.24; irBF rho −0.45), and the Mayo risk score correlated significantly with the total liver extraction capacity of Gd‐EOB‐DTPA (rho −0.85). Conclusion The study demonstrates a new method to quantify total and segmental liver function using DHCE‐MRI in patients with PSC. J. Magn. Reson. Imaging 2014;39:879–886. © 2013 Wiley Periodicals, Inc.